2020
DOI: 10.3390/cells9030603
|View full text |Cite
|
Sign up to set email alerts
|

PPE51 Is Involved in the Uptake of Disaccharides by Mycobacterium tuberculosis

Abstract: We have recently found that selected thio-disaccharides possess bactericidal effects against Mycobacterium tuberculosis but not against Escherichia coli or Staphylococcus aureus. Here, we selected spontaneous mutants displaying resistance against the investigated thio-glycoside. According to next-generation sequencing, four of six analyzed mutants which were resistant to high concentrations of the tested chemical carried nonsynonymous mutations in the gene encoding the PPE51 protein. The complementation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 50 publications
2
38
1
Order By: Relevance
“…The biological activity of fully protected per-acetylated thiodisaccharide 2 revealed that minimum inhibitory concentration (MIC50) for inhibition of Mycobacterium tuberculosis was observed at 0.05 mM level. 15 That important information on selective bactericidal inhibitory activity prompted us 16 to investigate the uptake mechanism of thiodisaccharide 2 identifying the role of PPE51 proteins (Pro-Pro-Glu (PPE) motif in their 110 and 180 amino acid N-terminal regions), which participates in the uptake process of thiodisaccharide 2 into Mycobacterium tuberculosis. This is a cornerstone discovery that provided evidence for a specific mechanism of action of inhibition of Mycobacterium tuberculosis by thiodisaccharides for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…The biological activity of fully protected per-acetylated thiodisaccharide 2 revealed that minimum inhibitory concentration (MIC50) for inhibition of Mycobacterium tuberculosis was observed at 0.05 mM level. 15 That important information on selective bactericidal inhibitory activity prompted us 16 to investigate the uptake mechanism of thiodisaccharide 2 identifying the role of PPE51 proteins (Pro-Pro-Glu (PPE) motif in their 110 and 180 amino acid N-terminal regions), which participates in the uptake process of thiodisaccharide 2 into Mycobacterium tuberculosis. This is a cornerstone discovery that provided evidence for a specific mechanism of action of inhibition of Mycobacterium tuberculosis by thiodisaccharides for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…As EspB shows a similar fold as PE/PPE dimers, this suggests that PE/PPE substrates might also oligomerize upon secretion and that EspG binding is required to prevent premature multimerization (96). In line with this hypothesis, several PE and PPE proteins have been shown to be firmly associated with the mycobacterial cell envelope (41,61,114). A final support for the role of specific PE/PPE proteins in OM translocation comes from M. smegmatis reconstitution experiments.…”
Section: Possible Mechanisms Of Outer Membrane Translocationmentioning
confidence: 85%
“…However, these porins are all absent in M. tuberculosis and other slowgrowing species. In M. tuberculosis, CpnT and SpmT, and more recently also specific PE/PPE proteins, have been found to mediate uptake of nutrients (33,61,97,114). However, structural information on the membrane-spanning domains of these proteins is still lacking (33,97).…”
Section: Possible Mechanisms Of Outer Membrane Translocationmentioning
confidence: 99%
“…EsaA is potentially analogous to EccB because it contains a large extracellular domain. In the case of the monoderm Firmicutes where no mycomembrane pore is required, the extracellular domain of EsaA is speculated to form a cell wall spanning conduit through which T7SSb substrates are exported to multimerize and may be similarly involved in export or even import across the mycomembrane, possibly via the formation of mycomembrane-spanning pores (Korycka-Machala et al, 2020;Piton et al, 2020;Solomonson et al, 2015;Wang et al, 2020).…”
Section: Ultrastructure Of the T7ssamentioning
confidence: 99%
“…Given that EspC is required for the secretion of EsxA, the authors of this study speculate that it may form a membrane‐spanning needle or pilus, similar to what is observed for some of the specialized secretion systems in Gram‐negative bacteria (Lou et al., 2017; MacGurn et al., 2005). Other T7SSa substrates, such as EspB and PPE51, also exhibit a propensity to multimerize and may be similarly involved in export or even import across the mycomembrane, possibly via the formation of mycomembrane‐spanning pores (Korycka‐Machala et al., 2020; Piton et al., 2020; Solomonson et al., 2015; Wang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%